Market Share Pioneering Advantage: A Theoretical Approach - Fershtman, Chaim; Mahajan, Vijay; Muller, Eitan (Management Science, 1990)
In this paper we present an industry in which a pioneer has entered, accumulated capital in the form of goodwill, and in his monopoly period has also reduced his cost of production as a result of some form of learning by doing. At some later date a newcomer enters. His production cost is higher than that of the monopolist at that date. However due to diffusion of information, the costs of the two firms equate at some future date. Once the new firm enters the market a duopolistic game begins in which the firms choose prices and investment rates. Analyzing this game we discover the conditions under which the final market shares no longer depend on the order of entry, the initial cost advantage, the length of the monopoly period, or the length of time it took the newcomer to overcome the pioneer's cost advantage. We analyze the speed and pattern of convergence to the final market shares and the capital path of the pioneer in his monopoly period, depending on his beliefs concerning the possibility of entry.